Ti-al-mn intermetallic compound, and preparation method and application thereof

CN122979702APending Publication Date: 2026-10-27BAOJI TITANIUM IND CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610987567.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

这一性能瓶颈限制了该低成本TiAl合金的工程化应用

Benefits of technology

[0017]1、本发明首次系统研究了0~2%Zr合金化对含锰β-γ-TiAl 合金循环氧化行为的影响,明确了Zr元素抗氧化作用的临界含量阈值,揭示了低含量Zr加剧氧化、高含量Zr提升抗氧化性能的差异化作用规律,填补了该领域的研究空白。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979702A_ABST
    Figure CN122979702A_ABST
Patent Text Reader

Abstract

The application discloses a Ti-Al-Mn intermetallic compound and a preparation method and application thereof. The composition of the compound is as follows in percentage by atom: Al 40-44%, Mn 1.0-5.0%, Zr 1.0-2.0%, and the balance of Ti and inevitable trace impurities. By adding 1.0-2.0% of Zr, the application solves the problem of insufficient high-temperature oxidation resistance of the existing Ti-Al-Mn alloy, significantly reduces the cyclic oxidation weight gain of the alloy at 800 DEG C, and inhibits the cracking and peeling of the oxidation film. The alloy can be prepared by a vacuum melting method and is suitable for manufacturing high-temperature workpieces in the fields of aeroengines, automobile engines and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of intermetallic compound technology, specifically relating to a Ti-Al-Mn intermetallic compound, its preparation method and application. Background Technology

[0002] TiAl-based alloys are ideal lightweight high-temperature structural materials to replace traditional nickel-based superalloys due to their low density, high specific strength, and excellent high-temperature creep resistance. Among them, Mnβ-solidified γ-TiAl alloys, represented by Ti-42Al-5Mn, stabilize the β phase by adding Mn, thus improving the solidification segregation problem of traditional TiAl alloys and exhibiting better hot working properties.

[0003] However, the introduction of Mn also leads to a decrease in the oxidation resistance of this alloy under high-temperature service conditions of 750 to 850°C. During high-temperature oxidation, it is difficult to form a continuous and stable Al2O3 protective film on the alloy surface; instead, a loose and porous TiO2 oxide layer forms. This oxide layer is prone to cracking and peeling under thermal cycling stress, repeatedly exposing the fresh substrate and accelerating the oxidation process. This performance bottleneck limits the engineering application of this low-cost TiAl alloy. Summary of the Invention

[0004] To solve the above technical problems, the present invention provides a Ti-Al-Mn intermetallic compound, wherein the composition of the Ti-Al-Mn intermetallic compound, in atomic percentage, is: Al 40% to 44%, Mn 1.0% to 5.0%, Zr 1.0% to 2.0%, with the balance being Ti and unavoidable trace impurities.

[0005] Preferably, the composition of the Ti-Al-Mn intermetallic compound, in atomic percentage, is: Al 42%, Mn 5%, Zr 1.0% to 2.0%, with the balance being Ti and unavoidable trace impurities.

[0006] Preferably, in a 100-hour cyclic oxidation test under static air atmosphere at 800°C, the Ti-Al-Mn intermetallic compound exhibits an oxidation weight gain of less than 1.15 mg / cm² per unit area, and the alloy oxide layer with 2% Zr addition shows no peeling.

[0007] This invention also discloses a method for preparing Ti-Al-Mn intermetallic compounds, the method comprising the following steps:

[0008] Raw materials containing Ti, Al, Mn, and Zr are provided based on atomic percentage;

[0009] The raw materials are vacuum melted, kept at a constant temperature and stirred before being poured to obtain an alloy ingot.

[0010] The alloy ingot was wire-cut, polished and cleaned to obtain the Ti-Al-Mn intermetallic compound sample.

[0011] Preferably, it is any one of vacuum induction melting, vacuum self-consumable melting, or induction solidification melting.

[0012] Preferably, during the smelting process, the vacuum level in the furnace cavity is lower than 1×10⁻⁶. -2 Pascal, filled with an inert gas as a protective atmosphere, the pressure of which is 0.04 MPa to 0.1 MPa.

[0013] Preferably, the raw materials include sponge titanium, industrial pure aluminum, pure manganese, and pure zirconium, wherein the purity of sponge titanium is not less than 99.7% by weight, and the purity of industrial pure aluminum, pure manganese, and pure zirconium is not less than 99.99% by weight.

[0014] This invention also discloses the application of a Ti-Al-Mn intermetallic compound in the manufacture of high-temperature oxidation resistant workpieces.

[0015] Preferably, the high-temperature oxidation-resistant workpiece is a valve of an automotive fuel engine, a turbine blade of an aero-engine gas turbine, a guide vane of an aero-engine gas turbine, a nose cone of a hypersonic vehicle, a leading edge of a wing of a hypersonic vehicle, or a structural component of an ultra-high temperature gas-cooled reactor in the nuclear industry.

[0016] The advantages and beneficial effects of this invention are as follows:

[0017] 1. This invention is the first to systematically study the effect of 0~2% Zr alloying on the cyclic oxidation behavior of manganese-containing β-γ-TiAl alloys, clarify the critical content threshold of Zr element for antioxidant effect, and reveal the differential effect law of low Zr content aggravating oxidation and high Zr content improving antioxidant performance, filling the research gap in this field.

[0018] 2. This invention, through alloying design with 1.0~2.0% Zr, achieves a significant improvement in the high-temperature cyclic oxidation resistance of Ti-Al-Mn alloys from four dimensions: promoting selective Al oxidation, refining oxide film grains, improving oxide film density, and inhibiting oxide film cracking and spalling. The addition of 2% Zr can reduce the oxide weight gain of the alloy by 44.8% and completely inhibit oxide layer spalling.

[0019] 3. The alloy preparation method provided by this invention is fully compatible with the existing industrial vacuum melting and hot working process of TiAl alloy. No new special equipment is required. The process is simple and controllable, and can be mass-produced. At the same time, it retains the excellent uncladding hot working performance of manganese-containing TiAl alloy, and takes into account the formability and high-temperature service performance of the material.

[0020] 4. The Zr-modified Ti-Al-Mn intermetallic compound developed in this invention has the advantages of low cost, easy processing and high oxidation resistance, and can be widely used in high-temperature service components in aerospace, automotive power and other fields, which has greatly promoted the engineering application of this type of TiAl alloy. Attached Figure Description

[0021] Figure 1 Oxidation mass gain curves of Ti-Al-Mn alloys with different Zr additions after 100 hours of cyclic oxidation at 800℃;

[0022] Figure 2 The image shows a scanning electron microscope (SEM) image of the surface oxide film of the alloy of Comparative Example 1 (0% Zr) after 100 hours of cyclic oxidation at 800 °C.

[0023] Figure 3 The image shows a scanning electron microscope (SEM) image of the surface oxide film of alloy Comparative Example 2 (0.5% Zr) after 100 hours of cyclic oxidation at 800 °C.

[0024] Figure 4 The image shows a scanning electron microscope (SEM) image of the surface oxide film of the alloy in Example 1 (1% Zr) after 100 hours of cyclic oxidation at 800°C.

[0025] Figure 5 This is a scanning electron microscope image of the surface oxide film of the alloy in Example 2 (2%Zr) after 100 hours of cyclic oxidation at 800°C. Detailed Implementation

[0026] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0027] First Embodiment

[0028] This embodiment provides a Ti-Al-Mn intermetallic compound and its preparation method. The composition of the compound, in atomic percentage, is: Al 42%, Mn 5%, Zr 1.0% to 2.0%, with the balance being Ti and unavoidable trace impurities. As a specific example of this embodiment, two alloys with Zr addition amounts of 1% and 2% were prepared, respectively.

[0029] Its preparation method includes the following steps:

[0030] Ingredient preparation steps: Calculate and weigh the raw materials according to the atomic percentages mentioned above. The raw materials include sponge titanium with a purity of not less than 99.7% by weight, industrial pure aluminum with a purity of not less than 99.99% by weight, pure manganese with a purity of not less than 99.99% by weight, and pure zirconium with a purity of not less than 99.99% by weight. The total input mass is 2.5 kg.

[0031] Vacuum melting step: Place the prepared raw materials into an alumina crucible and put it into a vacuum induction furnace. Evacuate the furnace chamber to 8×10⁻⁻⁻⁶. 3 The pressure is increased to Pascal, then high-purity argon gas (0.08 MPa) is introduced as a protective atmosphere. The induction heating power is gradually increased until the raw materials are completely melted. Electromagnetic stirring is then activated to ensure uniform mixing of the alloy liquid, and the mixture is held at this temperature for 10 minutes. This embodiment uses vacuum induction melting, but vacuum consumable melting or induction solidification melting can also be used.

[0032] Casting process: The alloy liquid is poured into a preheated metal mold using gravity casting to form a cylindrical ingot with a diameter of 80 mm and a length of 100 mm. The ingot is then demolded after being naturally cooled to room temperature in the furnace.

[0033] Sample preparation steps: A 10 mm × 10 mm × 5 mm cube sample was cut from the ingot using wire electrical discharge machining. Silicon carbide sandpaper was used to polish the sample from 180 grit to 1200 grit to remove wire cutting marks. The sample was ultrasonically cleaned in anhydrous ethanol for 20 minutes, then removed and dried with cold air to obtain a Ti-Al-Mn intermetallic compound sample.

[0034] Second Embodiment

[0035] This embodiment provides the application of Ti-Al-Mn intermetallic compounds as described in the first embodiment in the manufacture of high-temperature oxidation-resistant workpieces. These high-temperature oxidation-resistant workpieces can be automotive fuel engine valves, aero-engine gas turbine turbine blades, aero-engine gas turbine guide vanes, hypersonic vehicle nose cones, hypersonic vehicle wing leading edges, or nuclear industry ultra-high temperature gas-cooled reactor structural components.

[0036] The Ti-Al-Mn intermetallic compound prepared in the first embodiment (e.g., an alloy with a composition of 41% Ti, 42% Al, 5% Mn, and 2% Zr) is manufactured into the desired shape of the workpiece using conventional machining, casting, or powder metallurgy processes. Because this material possesses excellent oxidation resistance and the ability to inhibit oxide film peeling at 800°C, workpieces made from it can maintain structural integrity and performance stability under long-term high-temperature service conditions, thereby extending service life and improving equipment safety.

[0037] To verify the technical effectiveness of this embodiment, the following comparative tests were conducted.

[0038] Comparative Example 1 (Zr-free): A Zr-free Ti-Al-Mn matrix alloy was provided, with a composition of 43% Ti, 42% Al, and 5% Mn. The preparation method was the same as in the first embodiment, but pure zirconium was not added during the formulation.

[0039] Comparative Example 2 (0.5% Zr addition): A Ti-Al-Mn-Zr alloy with a Zr addition of 0.5% was provided, with a composition of 42.5% Ti, 42% Al, 5% Mn, and 0.5% Zr. The preparation method was the same as that of the first embodiment.

[0040] The performance of the samples from the first embodiment, the second embodiment, Comparative Example 1, and Comparative Example 2 described above was tested.

[0041] 1. High-temperature cyclic oxidation performance test

[0042] Test subjects: Samples prepared in Comparative Example 1, Comparative Example 2, Example 1, and Example 2;

[0043] Test equipment: KSL-1200X resistance furnace, QUINTIX125D-1CN analytical balance (accuracy 0.01 mg), and corundum crucible with lid;

[0044] Test conditions: 800℃ static air atmosphere, single cycle is 60 min heat preservation + 30 min air cooling, total cycle 100 times, total oxidation time 100 hours;

[0045] Test method:

[0046] Before the experiment, the corundum crucible was pre-fired at 900℃ to constant weight, and the net weight of the crucible was recorded. The sample was placed in the crucible, weighed, and the initial total weight of "crucible + sample" was recorded.

[0047] After every 10 cycles, remove the covered crucible and cool it to room temperature. Weigh and record the total weight of "crucible + sample + detached oxide scale" and calculate the cumulative weight gain due to oxidation.

[0048] After 100 cycles, the unit area oxidative weight gain and average oxidation rate of each group of samples were calculated, and the oxide scale peeling was statistically analyzed.

[0049] Test results:

[0050] The results of the cyclic oxidation performance test of each group of samples at 800℃ / 100h are shown in Table 1. The curves of oxidation mass gain versus time are shown in Table 1. Figure 1 .

[0051] Table 1: Results of Cyclic Oxidation Performance Test at 800℃ / 100 Hours

[0052]

[0053] From Table 1 and Figure 1As can be seen, the oxidation weight gain of Comparative Example 2, with the addition of 0.5% Zr (1.9600 mg / cm²), was even higher than that of Comparative Example 1 without Zr (1.8250 mg / cm²), indicating that low Zr content had a negative effect. In the first embodiment of this application, the oxidation weight gain of the sample with 1% Zr added decreased to 1.1475 mg / cm², and the oxidation weight gain of the sample with 2% Zr added further decreased to 1.0075 mg / cm², both below 1.15 mg / cm². This demonstrates that when the Zr addition is in the range of 1.0% to 2.0%, the high-temperature cyclic oxidation resistance of the alloy is significantly improved.

[0054] 2. Morphology of surface oxide film

[0055] Characterization objects: Comparative Example 1, Comparative Example 2, Example 1, and Example 2 samples after cyclic oxidation test;

[0056] Characterization equipment: Prisma E-type tungsten filament scanning electron microscope (SEM);

[0057] Characterization method: The oxide film on the sample surface was observed at low magnification using SEM to analyze the smoothness and continuity of the oxide film.

[0058] like Figure 2 As shown, the oxide film on the surface of the Comparative Example 1 (without Zr) sample is uneven, with obvious scaly warping and local peeling areas. The oxide film thickness is unevenly distributed, with peeling pits and some fresh substrate exposed.

[0059] like Figure 3 As shown, the oxide film on the surface of the Comparative Example 2 (0.5% Zr) sample was more severely peeled off, with a larger proportion of warped and detached areas, poorer surface smoothness, and even large areas of oxide layer peeling off entirely.

[0060] like Figure 4 As shown, in the first embodiment of this application, the sample with 1% Zr added has a smooth and continuous oxide film on its surface, without obvious warping or large-scale peeling, with only localized extremely small defects, and the oxide film thickness is uniformly distributed.

[0061] like Figure 5 As shown, in the first embodiment of this application, the sample with 2% Zr added has a smoother and flatter oxide film on its surface, with no warping, cracking or peeling. The entire surface is protected by a uniformly covered oxide film with no exposed substrate area.

[0062] The above test results verified the effect of Zr alloying with controlled Zr addition amounts of 0%, 0.5%, 1%, and 2% on the cyclic oxidation behavior of manganese-containing β-γ-TiAl alloys, clarifying that the critical addition threshold for Zr to improve the alloy's oxidation resistance is above 1%. The addition of 1.0–2.0% Zr can significantly improve the high-temperature cyclic oxidation resistance of the alloy by promoting selective Al oxidation, refining oxide film grains, improving oxide film density, enhancing the interfacial bonding between the oxide film and the substrate, and inhibiting oxide film cracking and spalling. This solves the core bottleneck of insufficient high-temperature oxidation resistance in manganese-containing TiAl alloys and provides a solid experimental foundation for the composition optimization and engineering application of this type of alloy.

[0063] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A Ti-Al-Mn intermetallic compound, characterized in that, The composition of the Ti-Al-Mn intermetallic compound, in atomic percentage, is: Al 40% to 44%, Mn 1.0% to 5.0%, Zr 1.0% to 2.0%, with the balance being Ti and unavoidable trace impurities.

2. The Ti-Al-Mn intermetallic compound according to claim 1, characterized in that, The composition of the Ti-Al-Mn intermetallic compound, in atomic percentage, is: Al 42%, Mn 5%, Zr 1.0% to 2.0%, with the balance being Ti and unavoidable trace impurities.

3. A Ti-Al-Mn intermetallic compound according to claim 1, characterized in that, In a 100-hour cyclic oxidation test under static air atmosphere at 800℃, the Ti-Al-Mn intermetallic compound showed an oxidation weight gain of less than 1.15 mg / cm², and the alloy oxide layer with 2% Zr addition did not exhibit peeling.

4. A method for preparing a Ti-Al-Mn intermetallic compound as described in any one of claims 1 to 3, characterized in that, The preparation method includes the following steps: providing raw materials of Ti, Al, Mn and Zr elements according to atomic percentage; vacuum melting the raw materials, keeping them warm and stirring them before casting to obtain an alloy ingot; wire cutting, grinding and cleaning the alloy ingot to obtain the Ti-Al-Mn intermetallic compound sample.

5. The method for preparing a Ti-Al-Mn intermetallic compound according to claim 4, characterized in that, The smelting method is any one of vacuum induction smelting, vacuum self-consumption smelting, or induction solidification smelting.

6. The method for preparing a Ti-Al-Mn intermetallic compound according to claim 4, characterized in that, During the smelting process, the vacuum level in the furnace cavity is less than 1×10⁻⁶. -2 Pascal, filled with an inert gas as a protective atmosphere, the pressure of which is 0.04 MPa to 0.1 MPa.

7. The method for preparing a Ti-Al-Mn intermetallic compound according to claim 4, characterized in that, The raw materials include sponge titanium, industrial pure aluminum, pure manganese, and pure zirconium, wherein the purity of sponge titanium is not less than 99.7% by weight, and the purity of industrial pure aluminum, pure manganese, and pure zirconium is not less than 99.99% by weight.

8. The application of a Ti-Al-Mn intermetallic compound as described in any one of claims 1 to 3 in the manufacture of high-temperature oxidation resistant workpieces.

9. The application according to claim 8, characterized in that, The high-temperature oxidation resistant workpieces are automotive fuel engine valves, aero-engine gas turbine turbine blades, aero-engine gas turbine guide vanes, hypersonic vehicle nose cones, hypersonic vehicle wing leading edges, or nuclear industry ultra-high temperature gas-cooled reactor structural components.